Cam Jansen and the mystery of the circus clown - Adler, David A.; Natti, Susanna (New York : Scholastic, 1985)
Fifth-grader Cam Jansen uses her photographic memory to help find a pick-pocket at the circus.
"A Yearling book."
Booklist
School Library Journal
Bulletin Of The Center For Children's Books
4.7
3-6
Keywords: Detective and mystery stories; Circus -- Fiction; Mystery and detective stories; Circus -- Fiction